2021
DOI: 10.1097/j.pain.0000000000002298
|View full text |Cite|
|
Sign up to set email alerts
|

Patient outcomes after opioid dose reduction among patients with chronic opioid therapy

Abstract: The net effects of prescribing initiatives that encourage dose reductions are uncertain. We examined whether rapid dose reduction after high-dose chronic opioid therapy (COT) associates with suicide, overdose, or other opioid-related adverse events. This retrospective cohort study included Oregon Medicaid recipients with high-dose COT. Claims were linked with prescription data from the prescription drug monitoring program and death data from vital statistics, 2014 to 2017. Participants were placed into 4 mutua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 36 publications
(44 reference statements)
5
41
0
Order By: Relevance
“…17 A study of Oregon Medicaid recipients found adjusted hazard ratios for suicide of 3.6 for discontinuation and 4.5 for tapering. 18 A study using the same claims data set and similar definition of long-term opioid therapy as our study identified effect estimates between those in our study and those in prior studies, with an estimated adjusted incidence rate ratio of 1.3 for the association of dose tapering with overdose and 2.4 for the association of dose tapering with suicide attempts. 32 The present study offers 2 key methodological advances in the study of opioid tapering.…”
Section: Jama Network Open | Substance Use and Addictionsupporting
confidence: 55%
See 1 more Smart Citation
“…17 A study of Oregon Medicaid recipients found adjusted hazard ratios for suicide of 3.6 for discontinuation and 4.5 for tapering. 18 A study using the same claims data set and similar definition of long-term opioid therapy as our study identified effect estimates between those in our study and those in prior studies, with an estimated adjusted incidence rate ratio of 1.3 for the association of dose tapering with overdose and 2.4 for the association of dose tapering with suicide attempts. 32 The present study offers 2 key methodological advances in the study of opioid tapering.…”
Section: Jama Network Open | Substance Use and Addictionsupporting
confidence: 55%
“…[12][13][14] Several observational studies have identified harms associated with opioid tapering and discontinuation, but they also have several limitations. [15][16][17][18] Many studies focused on opioid discontinuation, which is likely more destabilizing than gradual tapering. Furthermore, there is a high potential for confounding.…”
Section: Introductionmentioning
confidence: 99%
“…Patients receiving long-term, high-dosage opioid therapy for chronic pain are at increased risk for adverse events including overdose death ( 55 , 72 , 202 , 203 , 209 ). However, discontinuation of long-term, high-dosage opioid therapy has been associated with adverse events including mental health crisis, overdose events, and overdose death ( 71 73 , 210 , 211 ). In addition, opioid tapering has been found to be associated with subsequent termination of care ( 212 ).…”
Section: Recommendationsmentioning
confidence: 99%
“…We explored baseline characteristics previously shown to be associated with opioid tapering, discontinuation, dose variability, or overdose mortality. 6 , 17 , 29 , 30 , 31 , 32 Demographic characteristics included age on the index date, sex, and race and ethnicity as reported by patients during visit registration and recorded in the EHR. Race and ethnicity, Medicaid coverage, and the calendar year of the index date were assessed because they could impact management decisions and the outcomes.…”
Section: Methodsmentioning
confidence: 99%